KOMITMEN PEMIMPIN DALAM MENCIPTAKAN BUDAYA ORGANISASI UNTUK MENGHASILKAN KINERJA KARYAWAN (STUDI KASUS PADA PT. DWI SAPTA PRATAMA) - Erwin Erwin; Ryan Firdiansyah (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
The research objectives are: 1) To find out how much influence the commitment of leaders on employee performance at PT. Dwi Sapta Pratama. 2) To find out how much influence the organizational culture has on employee performance at PT. Dwi Sapta Pratama. 3) To find out how much influence the commitment of leaders and organizational culture together on employee performance at PT. Dwi Sapta Pratama. This research is quantitative, descriptive and associative type. The population in this study is employees. Related to research, the authors use the technique of Simple Random Sampling. With simple random sampling technique, a sample of 75 employees of PT. Dwi Sapta Pratama as a respondent in this study. The results of this study indicate that: 1) There is an influence of leader commitment on employee performance at PT. Dwi Sapta Pratama. 2) There is an influence of organizational culture on employee performance at PT. Dwi Sapta Pratama. 3) There is an influence of the commitment of leaders and organizational culture together on the performance of employees at PT. Dwi Sapta Pratama.